The Key Parameter Effect Analysis Of Polymer Flooding On Oil Recovery Using Reservoir Simulation - Erfando, Tomi; Rita, Novia; Ramadhan, Romal (UIR PRESS, 2019)
As time goes by, there will be decreasing of production rates of a field along with decreasing pressure. This led to the necessity for further efforts to increase oil production. Therefore, pressure support is required to improve the recovery factor. Supportable pressure that can be used can be either water flooding and polymer flooding. This study aims to compare recovery factor to scenarios carried out, such as polymer flooding with different concentrations modeled in the same reservoir model to see the most favorable scenario. The method used in this research is reservoir simulation method with Computer Modeling Group (CMG) STARS simulator. The study was carried out by observing at the pressure, injection rate, and polymer concentration on increasing field recovery factor. This study used cartesian grid with the assumption of homogeneous reservoir, there are no faults or other geological condition in the reservoir, and driving mechanism is only solution gas drive. This reservoir, oil type is light oil with API gravity 40.3˚API and layer of conglomerate rock. The simulation result performed with various scenarios provides a good result. Where the conditions case base case field recovery factor of 6.7%, and after water flooding produced 25.5% of oil, whereas with tertiary recovery method is polymer flooding was carried out with four concentrations of 640 ppm, 1,500 ppm, 3,000 ppm, and 4,000 ppm obtained optimum values at 4,000 ppm polymer concentration with recovery factor 28.9%, SOR reduction final value 0,5255, polymer adsorption of 818,700 ppm, reservoir final pressure 1,707 psi, and an increase in water viscosity to 0.94 cP.